Adequate vitamin A liver stores estimated by the modified relative dose response test are positively associated with breastfeeding but not vitamin A supplementation in Senegalese urban children 9-23 months old: A comparative cross-sectional study. - Mane Hélène Faye; Marie-Madeleine A Diémé; Nicole Idohou-Dossou; Abdou Badiane; Adama Diouf; Ndeye Magatte Ndiaye Ndome; Sherry A Tanumihardjo (PLoS ONE)
Vitamin A supplementation (VAS) in 6-59-month-old children is recommended but its sustainability is currently questioned. In Senegal, available data suggest that VAS should be maintained, but geographic and age-related specificities need to be addressed to better implement and target VAS programming. The objective of this comparative cross-sectional study, conducted in urban settings of Dakar, was to compare the vitamin A liver stores (VALS) assessed using the modified-relative dose response (MRDR) test between supplemented and non-supplemented 9-23 month-old children and to study their relationship with VAS. The supplemented group (n = 119) received VAS (either 100 000 UI or 200 000 UI) 2 to 6 months before evaluation while the non-supplemented group (n = 110) had not received VAS during the past 6 months. In addition to MRDR, serum retinol concentrations (SR), and biomarkers of subclinical inflammation were measured. Children's health-related data and feeding patterns were collected. Mean MRDR values (VAS: 0.030 ± 0.017, non-VAS: 0.028 ± 0.016, P = 0.389) and inflammation-adjusted SR (VAS: 1.34 ± 0.37, non-VAS: 1.3 ± 0.35, P = 0.515) of children were adequate. Low prevalence of VALS (VAS: 5.2%, non-VAS: 5.4%) and inflammation-adjusted VAD (VAS: 2.6%, non-VAS: 0.9%) were detected despite high presence of infections and inflammation. Children were mostly still being breastfed (VAS: 85.7%, non-VAS: 77.3%) and complementary feeding indicators were similar in both groups. Only breastfeeding was associated with VALS and was found to reduce by 76% at least, the odds of VAD (adjusted OR = 0.24, 95% CI: 0.07-0.8, P = 0.020). Based on MRDR values, VAS was not related to improved VALS and SR as well as VAD reduction among these children with adequate VALS. Reinforcing breastfeeding advocacy and morbidity prevention/control are essential in this setting. Scaling-back VAS in this subpopulation should be examined regarding the risk of hypervitaminosis A after an evaluation of dietary vitamin A intake sufficiency and a more quantitative assessment of VALS.